A simulation model for blood cholesterol dynamics and related disorders - Demirezen, Emre Muzaffer. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2009., 2009)
Cholesterol metabolism and other factors affecting its dynamics comprise a complex system which includes genetics of the person, diet, exercise, and drugs. High concentrations of cholesterol are related with higher risk of cardiovascular diseases, therefore cholesterol is the subject of many modeling studies. The purpose of these studies is generally identifying or quantifying some parameters, or testing some hypothesis about cholesterol mechanism. Focus of the simulation models are mostly at the cellular level, whereas mathematical models usually make several assumptions for the sake of analytical tractability. As such, these types of models do not typically adopt a systemic view. In this study, system dynamics method, which has a systemic view that other cholesterol studies lack, is employed in modeling and analyzing the dynamics of cholesterol metabolism. The goal of this thesis study is to construct a continuous dynamic simulation model that can generate long term dynamics of cholesterol in healthy and hypercholesterolemic subjects, taking into account body weight dynamics, diet, and exercise of the person. For both healthy and hypercholesterolemic subjects the model is able to generate realistic behaviors of different types of blood cholesterol, and body weight. In the scenario analysis section it is shown that a person can have healthier cholesterol levels by changing her/ his diet and/or doing more exercise. Also it's observed that exercise is more effective than diet even in the case when the subject does not lose weight. In the case of hypercholesterolemic patients, the model effectively mimics the way the drugs work and shows how the patient can reach healthier cholesterol levels..
Keywords: Cholesterol.